Recombination of knotted substrates by Tn3 resolvase. - Dröge, P (1989)
We studied the site orientation specificity for recombination by purified Tn3 resolvase. With standard plasmid substrates, resolvase acts only on directly repeated recombination sites. Knotting, however, makes inverted site substrates equally efficient. The structure of the knotted products of recombination shows that the DNA wrapped around resolvase in the synaptic intermediate has the same local geometry as the standard substrate but is reversed in topological sign. Similarly, the same strand exchange with the two substrates generates supercoils with opposite signs. Thus, DNA geometry rather than topology is critical for these features of recombination. The knotted inverse substrate like the direct site substrate must be (-) supercoiled under standard reaction conditions. However, under conditions in which supercoiling is not required, the structure of the knotted product is apparently the same. This indicates that the unique direction of strand exchange is determined by the structure of the synaptosome and not by (-) supercoiling of the substrate.